Flv3A facilitates O2 photoreduction and affects H2 photoproduction independently of Flv1A in diazotrophic Anabaena filaments. Issue 1 (11th October 2022) - Santana‐Sánchez, Anita; Nikkanen, Lauri; Werner, Elisa; Tóth, Gábor; Ermakova, Maria; Kosourov, Sergey; Walter, Julia; He, Meilin; Aro, Eva‐Mari; Allahverdiyeva, Yagut
Summary: The model heterocyst‐forming filamentous cyanobacterium Anabaena sp. PCC 7120 ( Anabaena ) is a typical example of a multicellular organism capable of simultaneously performing oxygenic photosynthesis in vegetative cells and O2 ‐sensitive N2 ‐fixation inside heterocysts. The flavodiiron proteins have been shown to participate in photoprotection of photosynthesis by driving excess electrons to O2 (a Mehler‐like reaction). Here, we performed a phenotypic and biophysical characterization of Anabaena mutants impaired in vegetative‐specific Flv1A and Flv3A in order to address their physiological relevance in the bioenergetic processes occurring in diazotrophic Anabaena under variable CO2 conditions. We demonstrate that both Flv1A and Flv3A are required for proper induction of the Mehler‐like reaction upon a sudden increase in light intensity, which is likely important for the activation of carbon‐concentrating mechanisms and CO2 fixation. Under ambient CO2 diazotrophic conditions, Flv3A is responsible for moderate O2 photoreduction, independently of Flv1A, but only in the presence of Flv2 and Flv4. Strikingly, the lack of Flv3A resulted in strong downregulation of the heterocyst‐specific uptake hydrogenase, which led to enhanced H2 photoproduction under both oxic and micro‐oxic conditions. These results reveal a novel regulatory network between the Mehler‐like reaction and the diazotrophic metabolism, which is of great interest for future biotechnological applications.